PENERAPAN MODEL PEMBELAJARAN DUA TINGGAL DUA TAMU UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 20 PEKANBARU - Muharnis Hangraini; Munjiatun Munjiatun; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This study was motivated by the percentage of students who achieve KKM 70 at mid even semester from 2014 to 2015 is even lower. Of the 32 students only 13 (40.63%) of students who reach KKM and 19 (59.37%) students who have not reached KKM with an average of 71.83. This is because teachers rarely used learning models during the learning process in the classroom. From these problems need to be done to implement the action research model of cooperative learning type Two Stay Two guest. Where the research is in SD Negeri 20 Pekan Baru with the research subjects are students of class IV and as many as 32 people, male students and 17 female students 15 people. This study was carried in 2 cycles. Instrument collecting data in this study is the observation sheet teacher activity, student activity observation sheet and test sheet daily tests. Observation results showed that the activity of teachers and students has increased. The activities of teachers in the first cycle both categories increased 61.60% in the second cycle to 81.25% very good category. Activity of students in the first cycle both categories increased 61.61% in the second cycle into 82.14% very good category. The results showed that the learning outcomes of students has increased, the initial score with an average of 64.34, the category of incomplete increased in the first cycle to 68.75 categories is not exhaustive, and the second cycle increased to 76.86 category completely. Mastery learning students in the first cycle showed that 62.50% of students who reach the KKM has been established, on the second cycle increased to 81.25% of students who reach KKM and a predetermined percentage of completeness. From the above shows that through the implementation of cooperative learning type Two Stay Two guests may improve learning outcomes IPS students of class IV B Elementary School Lesson 20 Pekanbaru in educational year of 2014-2015Keywords: Cooperative Learning Model Two Stay Two Guest, IPS Learning Outcomes